Pengaruh Penggunaan Sosial Media, Pendidikan Kewirausahaan, Dan Literasi Keuangan Terhadap Perilaku Berwirausaha Online Pada Siswa SMK Negeri 1 Pangkalan Bun - Assha Firsticha Cahayaningrum; Susanti Susanti (Universitas Hamzanwadi, 2021)
This study aims to determine the results of the influence of social media use, entrepreneurship education, and financial literacy on online entrepreneurial behavior. This study used a quantitative study with a population of class XI and XII students in accounting and finance at the SMK Negeri 1 Pangkalan Bun. Sampling using purposive sample with 70 respondents. Data collection techniques using questionnaires and tests. Using descriptive analysis techniques and multiple linear regression analysis with the classical assumption test, namely normality test, multicollinearity test, heteroscedasticity test using SPSS. The results of this study are 1) the use of social media, entrepreneurship education, and financial literacy simultaneously influence online entrepreneurial behavior with Fcount of 29.925 Ftable 2.73 and a significance of 0.000 0.05. 2) The use of social media has a partially positive and significant influence on online entrepreneurial behavior with a significance of 0.001. 3) Entrepreneurship education has a partially positive and significant influence on online entrepreneurial behavior with a significance of 0.000. 4) Financial literacy has a partially positive and significant influence on online entrepreneurial behavior with a significance of 0.002